2017
DOI: 10.1186/s13065-017-0328-7
|View full text |Cite
|
Sign up to set email alerts
|

A review of phytochemistry, metabolite changes, and medicinal uses of the common sunflower seed and sprouts (Helianthus annuus L.)

Abstract: The sunflower (Helianthus annuus L.) seed and sprout is a ubiquitous crop with abundant nutrients and biological activities. This review summarizes the nutritional and medical importance currently recognized but under-researched concerning both seed and sprout highlighting the potential benefits of their phytochemical constituents including phenolic acids, flavonoids and tocopherols. Furthermore, the dynamic metabolite changes which occur during germination and biological activities are evaluated. The aim is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
88
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 79 publications
3
88
2
5
Order By: Relevance
“…5-Caffeoylquinic acid (chlorogenic acid) is the major phenolic compound accounting for 70 % of the TPC content, while the remaining 30 % are other mono-and di-caffeoylquinic acids, as well as coumaroyl-and feruloylquinic acids. Free caffeic (CA) acid is also found in SFM but accounts for just 0.5 % of the TPC content (Guo et al, 2017;Szydłowska-Czerniak et al, 2011;Weisz et al, 2009). Phenolic acids, particularly hydroxycinnamic acids, are bioactive molecules with interesting properties that include antioxidant (Gullón et al, 2018;Shahidi and Ambigaipalan, 2015), anti-inflammatory (Oueslati et al, 2012) and antimicrobial (Ouerghemmi et al, 2017) activities among others.…”
mentioning
confidence: 99%
“…5-Caffeoylquinic acid (chlorogenic acid) is the major phenolic compound accounting for 70 % of the TPC content, while the remaining 30 % are other mono-and di-caffeoylquinic acids, as well as coumaroyl-and feruloylquinic acids. Free caffeic (CA) acid is also found in SFM but accounts for just 0.5 % of the TPC content (Guo et al, 2017;Szydłowska-Czerniak et al, 2011;Weisz et al, 2009). Phenolic acids, particularly hydroxycinnamic acids, are bioactive molecules with interesting properties that include antioxidant (Gullón et al, 2018;Shahidi and Ambigaipalan, 2015), anti-inflammatory (Oueslati et al, 2012) and antimicrobial (Ouerghemmi et al, 2017) activities among others.…”
mentioning
confidence: 99%
“…Sunflower remains a source of nutritional food for humans. Studies have revealed that sunflower seeds are rich nutrients and certain different phytochemicals such as antioxidants, flavonols, phenolic acids, procyanidins, phytosterols, amino acids, dietary fiber, potassium, arginine monounsaturated, and polyunsaturated fatty acids which contribute to the improvement of human health (Alagawany, Farag, Abd El‐Hack, & Dhama, 2015; Guo, Ge, & Jom, 2017; Islam, Hossain, Majumder, & Tipu, 2016). According to literature, the antioxidant activity of phenolic compounds in sunflower seed has been reported (Menzel, González‐Martínez, Chiralt, & Vilaplana, 2019; Ye, Liang, Li, & Zhao, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sunflower seeds are the fruit of the sunflower which are grown worldwide and contains amazing health benefits owing to include valuable nutritional components ( Figure 1) [1]. Sunflower seeds are healthy snake when hunger.…”
Section: Introductionmentioning
confidence: 99%